Parallel gene expression evolution in natural and laboratory evolved populations. Issue 4 (12th October 2020) - Hsu, Sheng‐Kai; Belmouaden, Chaimae; Nolte, Viola; Schlötterer, Christian
Abstract: Ecological adaptation is frequently inferred by the comparison of natural populations from different environments. Nevertheless, inference of the selective forces suffers the challenge that many environmental factors covary. With well‐controlled environmental conditions, experimental evolution provides a powerful approach to complement the analysis of natural populations. On the other hand, it is apparent that laboratory conditions differ in many ways from natural environments, which raises the question as to what extent selection responses in experimental evolution studies can inform us about adaptation processes in the wild. In this study, we compared the expression profiles of replicated Drosophila melanogaster populations which have been exposed to two distinct temperature regimes (18/28 and 10/20°C) in the laboratory for more than 80 generations. Using gene‐wise differential expression analysis and co‐expression network analysis, we identified 541 genes and three coregulated gene modules that evolved in the same direction in both temperature regimes, and most of these changes probably reflect an adaptation to the space constraint or diurnal temperature fluctuation that is common in both selection regimes. In total, 203 genes and seven modules evolved temperature‐specific expression changes. Remarkably, we detected a significant overlap of these temperature‐adaptive genes/modules from experimental evolution with temperature‐adaptive genes inferred from natural Drosophila populations covering two different temperature clines. We conclude that well‐designed experimental evolution studies are a powerful tool to dissect evolutionary responses. Abstract : see also the Perspective by Mark A. Phillips and Molly K. Burke.